Pneumonia caused by Sphingomonas paucimobilis infection after a dental intervention - Jelena Janković; Milija Gajić; Andrej Zečević; Ivan Milivojević; Ivana Buha (Journal of Infection in Developing Countries)
Introduction: Sphingomonas paucimobilis can be found in air, water systems, dialysis fluid, nebulizers and laboratory instruments in hospitals. Despite its low pathogenicity, it can cause severe infections.